Development of A Workplace Learning Model to Improve Skills Competency of Vocational School Students - Rahmawati, Yulia (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims to develop a workplace learning model to improve the catering skills of tourism vocational school students by building a conceptual foundation that considers the industrial situation. This development research uses Design-Based Research (DBR) comprising planning, learning interactions, and evaluation stages for students, supervisors, and instructors. This study analyzes data using qualitative and quantitative descriptive methods. This research produces industrial practical learning tools (WPL) in the form of guidebooks for teachers, instructors and students. How to study in industry, the implementation process, ideal criteria, and completion of study contracts are outlined. Increasing student catering skills competency through industrial learning based on a measurable field approach. How students can absorb, adopt tacit and explicit knowledge in industry is a value in itself. Research findings and concepts can be used for further development so that the quality of vocational education graduates can be considered.